Analysing the prospect of the IAR4D's innovation platforms in improving the productive efficiencies of cereal-legume farmers in the Sudan Savanna of Nigeria - Olarinde, L.O.; Abdoulaye, Tahirou; Kamara, A.; Binam, J.; Adekunle, A. (2010)
This paper analysed the baseline productive efficiencies of the cereal–legume farmers in the Sudan Savanna of Nigeria. The paper also investigated the factors that affected the technical efficiency of the sampled farmers. Baseline data collected on cereal-legume farmers who belong to four Innovation Platforms were used for analysis. Results showed that sorghum-legume farmers obtained higher crop output, which is higher than the average for the total sample. There is decreasing return-to-scale in farming operations in the study area, however, unit increases in cultivated area, seed use and fertilizer/chemical application will improve the output by 17%, 20% and 29%, respectively. The mean technical efficiencies for the maize-legume, sorghum-legume farmers and for the pooled sample were found to be 85%, 74% and 79%, respectively. The frequencies of occurrence of the predicted technical efficiencies indicate that the highest number of farmers (for the total sample) have technical efficiencies between 80% and 90%. The sample frequency distribution indicates a clustering of technical efficiencies in the region of 0.8-0.9 efficiency range, implying that the farmers are fairly efficient. Given the variation in the level of technical efficiency, there appears to be considerable room for effecting improvements in the technical efficiencies of the farmers in the study area. Factors influencing technical inefficiency of farmers in the study area are age of farmers, farming experience, credit access, extension contact and interaction with other farmers and farmers’ groups, implying that being an IP member will help improve productive efficiencies. The results of this study have clearly demonstrated that almost all the hypothesized factors affecting the productive efficiencies of the sampled farmers are significant; an improvement in farmers’ productivity will be recorded if a reinforcement of the IP activities that are aligned with the findings here is ensured. This will increase the potential of the IAR4D to help in improving the productive efficiencies of the farmers, which is one of its key objectives.